Implementasi Algoritma Haversine Formula Pada Aplikasi Sadewa (Sistem Informasi Destinasi Wisata) Kota Salatiga Berbasis Android - Yusuf Ma'iin Rohmatulloh; Bambang Agus Herlambang; Setyoningsih Wibowo (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
Abstract - Salatiga is a city in Central Java Province which is located in the middle of two big cities, namely Semarang City which are 49 km away and Surakarta City which is 52 km away. During the colonialism, the Dutch government dubbed Salatiga as "De Schoonste Stad van Midderi-Javaborder" or the most beautiful city in Central Java. At this time the government of Salatiga City is working to make Salatiga again the most beautiful city in Central Java by making development efforts to beautify the city. To support this program, an information technology is needed to improve information about tourism. Tourists who will visit to need information on the nearest tourist destination to plan a trip to a tourist destination. The search for the nearest location can be applied using one of the algorithms, namely the Haversine Formula algorithm. This study uses Google Maps to display location routes. In terms of a utilization, it is hoped that this information system can make it easier for tourists to visit tourist destinations in Salatiga City.